Do staggered boards harm shareholders? - Amihud, Yakov; Stoyanov, Stoyan (Journal of Financial Economics, 2017)
We examine the Cohen and Wang (2013) conclusion that a staggered board lowers firm value based on the stock price reaction to two 2010 Delaware court rulings in the Airgas, Inc. case. The first ruling weakened the potency of a staggered board and the second restored it. We find that the Cohen and Wang results, for their sample, become insignificant after excluding a few penny stocks, stocks with value below $10 million, or over-the-counter (non-exchange) stocks. The effects of the rulings are also insignificant for an alternative sample.